Lifting as We Climb: Recognizing Intersectional Gender Violence in Law - Shreya Atrey (Oñati Socio-Legal Series)
This paper interrogates the meaning of lifting all women as we climb the ladder of gender equality and justice by recognizing that gender violence affects women differently. This is because violence against women is perpetrated not only on the basis of their gender or sex but also other identities of race, religion, caste, region, age, disability, nationality, sexual orientation etc. With reference to CEDAW jurisprudence and examples from India, I seek to explain this understanding with the help of a normative framework of ‘intersectional integrity’. The framework insists on considering claimants as a whole by tracing unique and shared patterns of gender violence when it is also based on other identities such as race, religion, caste, region, age, disability, nationality, and sexual orientation. I argue that applying the framework allows us to diagnose and address the nature of violence suffered on multiple identities, in a clear and comprehensive way.